Socially engaged design: a critical discussion with reference to an Egyptian Village. Issue 1 (2nd July 2016) - Willis, Anne-Marie; Elbana, Eman
Abstract: Designers are often impatient to get down to 'designing solutions' before the fundamental problem is actually identified and the situation sufficiently explored. In this paper, we do not approach 'socially engaged design' by asking 'what should be designed?' Instead, we argue for the necessity for designers to spend time gaining an understanding of the circumstances in which they seek to design and that bear upon the possibility of taking action. The aim is to contribute to more effective modes of socially engaged design by attempting to better understand its contexts and challenges. This is done via a 'problem-finding' exercise related to a village in Egypt's Nile River delta, interwoven with critical discussion of certain forms of socially engaged design and the theories of economic and social development that frame it.